Toward a More Perfect Union: Increasing Student Assistant Efficacy through an Online Training Program - Minniear, Jacob; Hornbaker, Jennifer (Issues in Language Instruction, 2012)
Using domestic student teaching assistants (SAs) in the ESOL classroom has been widely accepted as an effective tool for enhancing student learning. SAs have been shown to facilitate student participation in the classroom, foster students’ confidence in interacting with native speakers, and serve as a connection to the local culture (Lynch & Anderson, 2001). To capitalize on the benefits afforded by SAs, the AEC has, since 2007, integrated SAs into level one courses. However, research literature underscores that, to maximize SA efficacy, SAs must be purposefully trained for their roles (Gube & Phillipson, 2011; Kachi & Choon-hwa, 2001; Underhill & McDonald, 2010; Williams, 1991). As new GTAs, we observed that the AEC’s SAs represent a broad range of personalities, facilities, and experiences. Given these variances in SAs’ skills, we found ourselves questioning to what standard of knowledge we could and should hold them. Defining such a standard would enable teachers to design class activities that most productively draw upon the strengths of SAs without overstepping the boundaries of their expertise. Three lines of inquiry arose out of this realization: 1) What are the expectations of SAs at the AEC? 2) Do the AEC’s current, procedure-focused SA training practices satisfactorily prepare SAs to meet these expectations? If not, 3) how can the training program be improved to make the presence of SAs in the classroom more fruitful for students, teachers, and SAs alike?